2D Single‐Crystalline Molecular Semiconductors with Precise Layer Definition Achieved by Floating‐Coffee‐Ring‐Driven Assembly. (23rd March 2016) - Wang, Qijing; Qian, Jun; Li, Yun; Zhang, Yuhan; He, Daowei; Jiang, Sai; Wang, Yu; Wang, Xinran; Pan, Lijia; Wang, Junzhuan; Wang, Xizhang; Hu, Zheng; et al.
Abstract : 2D organic materials with in‐plane van der Waals forces among molecules have unique characteristics that ensure a brilliant future for multifunctional applications. Soluble organic semiconductors can be used to achieve low‐cost and high‐throughput manufacturing of electronic devices. However, achieving solution‐processed 2D single‐crystalline semiconductors with uniform morphology remains a substantial challenge. Here, the fabrication of 2D molecular single‐crystal semiconductors with precise layer definition by using a floating‐coffee‐ring‐driven assembly is presented. In particular, bilayer molecular films exhibit single‐crystalline features with atomic smoothness and high film uniformity over a large area; field‐effect transistors yield average and maximum carrier mobilities of 4.8 and 13.0 cm 2 V −1 s −1, respectively. This work demonstrates the strong potential of 2D molecular crystals for low‐cost, large‐area, and high‐performance electronics. Abstract : The floating‐coffee‐ring‐driven assembly of 2D single‐crystalline molecular semiconductors with precise layer definition is presented. Typical single‐crystalline features, atomic smoothness, and high morphologic uniformity over a large area are achieved. Field‐effect transistors devices yield a maximum carrier mobility of 13.0 cm 2 V −1 s −1 and thus show promise for low‐cost, large‐area, and high‐performance electronics.